Konstruksi Pengaturan Kekerasan Berbasis Gender Online Di Indonesia - Fadillah Adkiras; Fatma Reza Zubarita; Zihan Tasha Maharani Fauzi (Universitas Islam Indonesia, 2021)
This paper is motivated by problems related to the legal settlement mechanism for Online Gender Based Violence (KBGO) in Indonesia. KBGO is violence that attacks gender and/or sexuality facilitated by internet technology. Basically KBGO is very close to people's lives today. However, as with sexual violence cases in the offline realm, the number of recorded and resolved KBGO cases is only a fraction of the total number of real cases. This is further exacerbated because the resolution of the KBGO case is only limited to the use of the ITE Law and the Pornography Law. Even today, there is still no specific regulation that regulates it. The formulation of the problems raised in this research are first, how are the obstacles and challenges in the legal settlement of KBGO in Indonesia; second, how is the legal settlement mechanism for KBGO in Indonesia. The research method used in this study is juridical normative by using a statutory, conceptual, and comparison approach with other countries. The results of the study conclude, first, the obstacles and challenges in the completion of the KBGO are the existence of a legal vacuum that results in inconsistencies in the application of judge's decisions. Second, there is a need for a legal settlement mechanism for KBGO in Indonesia by classifying penal and non-penal mechanisms.Keyword : Legal constructions; KBGO; vaccum of lawAbstrakTulisan ini dilatarbelakangi adanya permasalahan terkait mekanisme penyelesaian hukum Kekerasan Berbasis Gender Online (KBGO) di Indonesia. KBGO adalah kekerasan yang menyerang gender dan/atau seksualitas yang difasilitasi oleh teknologi internet. Pada dasarnya KBGO sangat dekat dengan kehidupan masyarakat saat ini. Namun, sebagaimana kasus kekerasan seksual di ranah offline jumlah kasus KBGO yang tercatat dan terselesaikan hanya sepersekian dari jumlah total realita kasus yang ada. Hal ini semakin diperparah dikarenakan penyelesaian kasus KBGO hanya terbatas pada penggunaan UU ITE dan UU Pornografi. Bahkan sampai saat ini, masih belum ada peraturan khusus yang mengaturnya. Rumusan masalah yang diangkat dalam penelitian ini adalah pertama, bagaimana hambatan dan tantangan dalam penyelesaian hukum KBGO di Indonesia; kedua, bagaimana mekanisme penyelesaian hukum KBGO di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah normatif yuridis dengan menggunakan pendekatan peraturan perundang-undangan, konseptual, dan perbandingan dengan negara lain. Hasil penelitian menyimpulkan, pertama, hambatan dan tantangan dalam penyelesaian KBGO adalah masih adanya kekosongan hukum yang mengakibatkan inkonsistensi dalam penerapan putusan hakim. Kedua, perlu adanya mekanisme penyelesaian hukum KBGO di Indonesia dengan cara mengklasifikasikan mekanisme penal dan non penal.Kata Kunci : KBGO; kekosongan hukum; konstruksi hukum